1994
DOI: 10.1002/cne.903430108
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of vimentin‐positive cells in the rabbit superior colliculus

Abstract: The present study examined the postnatal development of the radial glia in the rabbit superior colliculus during the first 40 postnatal days. An antivimentin monoclonal antibody and the carbocyanine fluorescent tracer DiI were used in order to investigate the development of laminar connectivity in the superior colliculus. We focused our study on the superficial gray layer, the intermediate layer, and the deep layers of the superior colliculus, the periaqueductal gray matter (PAGM), and the medial intercollicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…These morphological changes of vimentin-immunoreactivity are similar to those reported in the VZ of the cerebral cortex [3,8,25,29] and periaqueductal gray matter [26,34]. Previous immunohistochemical studies using other antibodies as a radial glial marker, such as RC1 and RC2 [7,10,20,21], have also reported similar sequential changes in radial glia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These morphological changes of vimentin-immunoreactivity are similar to those reported in the VZ of the cerebral cortex [3,8,25,29] and periaqueductal gray matter [26,34]. Previous immunohistochemical studies using other antibodies as a radial glial marker, such as RC1 and RC2 [7,10,20,21], have also reported similar sequential changes in radial glia.…”
Section: Discussionsupporting
confidence: 84%
“…In rodents, this transformational change is thought to be accompanied by an alteration of intermediate filament proteins, from vimentin to glial fibrillary acidic protein (GFAP) [5,12,25]. Examples of radial glial transformation outside the cerebral cortex have been reported in the superior colliculus [26,27], hypothalamus [8,31], brainstem [8] and cerebellum [30,35,36]. Using vimentin-immunohistochemistry, Pulido-Caballero et al [27] reported on the appearance of vimentin-positive rosary-bead-like fibers in the rabbit superior colliculus during the period of radial-glial transformation and proposed that the segmentation of vimentin-positive fibers was a novel form of radial glial transformation.…”
Section: Introductionmentioning
confidence: 99%
“…These observations may explain the differences in axonal branching between deafferented neonates and adults. Indeed, we also found that immature vimentin-expressing astrocytes are abundant in the neonatal SC [47], where they may induce local sprouting after retinal deafferentation.…”
Section: Differential Lesion Responses Of Neonatal and Adult Visual Csupporting
confidence: 59%
“…Even though vimentin has been found in immature cells of the astroglial lineage in mammals (Elmquist et al 1994 ;Pulido-Caballero et al 1994) and reptiles (Monzon-Mayor et al 1990 ;Yanes et al 1990), it is still present in adult glial cells in teleosts and amphibians (Zamora & Mutin, 1988 ;Cardone & Roots, 1990 ;Rubio et al 1992 ;Lazzari et al 1997). Furthermore, vimentin is highly conserved in phylogenesis as suggested by the cross reaction of antibodies produced against mammalian vimentin with the corresponding protein in birds and amphibians (Bennett et al 1978 ;Szaro & Gainer, 1988 ;Zamora & Mutin, 1988 ;Bodega et al 1994).…”
mentioning
confidence: 99%